Boss ex machina: employer powers in workplaces governed by algorithms and artificial intelligence - Aloisi, Antonio (Giappichelli, 2023)
Is the existing legal framework suitable for “algorithmic bosses”? What if technology ends up disrupting the traditional limits of the legitimate managerial powers? The overarching goal of this paper is to determine whether digital automation has resulted in the augmentation of the organisational, control and disciplinary prerogatives of employers, managers and supervisors. Prior to validating the hypothesis of the magnification of powers, which gives rise to what we call boss ex machina, it is worth examining the spectacular extravagance of the contract of employment. If viewed through the lens of power, the employment relationship is structurally ambivalent because it both enables a condition of employer supremacy and tones it down through mandatory provisions, process-based restraints and collectively negotiated counterweights. This entire system of “controlling factors” is currently experiencing sustained stress. Using plain language, this paper is structured into four sections. Section 2 reflects on the apparent aims of the employment relationship by disentangling the meaning of the dominant position held by employers. Building on this, Section 3 catalogues the most widespread technologies currently invading the workplace and argues that, despite their heterogenous usages, the common denominator is the possibility of capturing and elaborating information that can be used to support managers in making executive decisions. Section 4 establishes the perils of the augmentation of managerial prerogatives through the adoption of automated decision-making. Taking a multidimensional approach, it also introduces remedies from data protection and non-discrimination law that could be read in conjunction with employment legislation to tame these rampant algorithmic bosses. Section 5 wraps up the chapter and offers some concluding remarks.
Keywords: Automated decision-making; Artificial intelligence; Algorithmic management; Employer powers; Surveillance; Data protection; Non-discrimination; ODS 8 - Trabajo decente y crecimiento económico